Hands-off, artificial construction, or penalty? How to deal with the increasingly polluted coastal wetland ecosystem in China - Bai, Yuntao; Ma, Shuai; Li, Delong (Frontiers in Ecology and Evolution, 2023)
As the destruction of coastal wetlands in China becomes more and more serious, the government needs to strengthen the management of wetland ecosystem. Considering that pollution is an important factor in the destruction of coastal wetlands in China, the government can deal with the problem of wetland pollution through three modes: hands-off, artificial construction and penalty. In this article, the differential game model is constructed under the three modes of hands-off, artificial construction and penalty. The balanced social benefits of the government and polluting enterprises under the three modes are obtained, and the applicable conditions of various wetland treatment paths are compared. The results show that when the revenue generated by taxation is small and the indirect income generated by artificial construction is small, the government will choose the laissez-faire mode. However, with the gradual increase of indirect income generated by artificial construction, the government will be inclined to choose the artificial construction mode. When the income from government fines is small, the social benefits of polluters in the hands-off mode are greater than those in the penalty mode. With the increase of fines, the social benefits of polluting enterprises will first decrease and then increase, which will eventually be greater than the social benefits under the hands-off mode.